Study on Form-Finding of Cable-Membrane Structures Based on Particle Swarm Optimization Algorithm. (30th April 2020) - Sun, Fangjin; Zhu, Donghan; Liang, Meirong; Zhang, Daming
Abstract : Form-finding is one of the key steps in the whole design process of cable-membrane structures. Traditional form-finding methods are usually complicated and have poor accuracy or stability. Thus, form-finding of cable-membrane structures based on particle swarm optimization (PSO) algorithm is proposed. The shape and loading characteristics of cable-membrane structures are optimized. The optimization objective is to minimize the maximum support reaction, and the initial prestress on the membrane surface is taken as the optimization variable. The main constraints are material strength limitation, structural stress, and displacement of the cable and membrane. A program is given based on the proposed PSO, and the optimization model and calculation process are implemented based on MATLAB and ANSYS platforms. Form-finding of three typical cable-membrane structures including rotating catenary surface, saddle surface, and rhombic hyperboloid is carried out. The results compare well with those from the force density method. The initial prestresses of the three membrane structures are obtained while the form-finding result is optimal, respectively. The proposed PSO shows a more accurate method in form-finding of cable-membrane structures in a simpler way.